Zooplankton Size Structure in Relation to Environmental Factors in the Xiangxi Bay of Three Gorges Reservoir, China - Li, Haoran; Gu, Yuan; Cai, Qinghua; Dong, Xiaowei; Ye, Lin (Frontiers in Ecology and Evolution, 2022)
Body size is sensitive to environmental changes and one of the fundamental traits linking ecological functions. Size structure has been suggested as a useful indicator for environmental monitoring and assessment in aquatic ecosystems. However, the organisms’ size structure and the relationship with environmental factors remain seldom addressed in reservoir ecosystems. In this study, we investigated the size spectrum, size diversity of the zooplankton and their relationships with environmental conditions across nitrogen and phosphorus gradients in the Xiangxi Bay of Three Gorges Reservoir, China. We further tested the hypotheses that how nutrient and water temperature affect zooplankton size structure: nutrients indirectly affect zooplankton size spectrum and size diversity via phytoplankton (H1); increasing water temperature will reduce size diversity and result in a steeper size spectrum (H2); size diversity is a more robust metric indicating environment changes than the size spectrum in high dynamic ecosystems (H3). We found that both the size spectrum and size diversity showed high spatiotemporal dynamics. The size spectrum ranged from -3.373 to -0.984. The size diversity ranged from 0.631 to 3.291. Spatially, the lowest values of the size spectrum and size diversity were observed in the upstream areas of Xiangxi Bay, where nitrogen and phosphorus concentrations are high and low, respectively. And in temporal dynamics, lower values of the size spectrum and size diversity were generally observed in March and April. Further analyses based on the structural equation model (SEM) found a clear pathway revealing that nutrient variables affect the zooplankton abundance and size structure, supporting hypothesis H1. That is, dissolved inorganic nitrogen had an indirect effect on the zooplankton abundance, size spectrum, and size diversity by influencing the concentration of phytoplankton chlorophyll a. In addition, results of SEM suggested that increased water temperature had a significant negative effect on the size diversity but had nonsignificant effects on zooplankton abundance and size spectrum. This finding suggests that size diversity is a reliable and useful index in measuring the zooplankton size structure in reservoir ecosystems with high dynamics, which may have a wide application in environmental monitoring and assessment, especially for complex and dynamic aquatic ecosystems.